Use of three-dimensional ultrasonography for the analysis of the fascicle length of human gastrocnemius muscle during contractions - Kurihara, T.; Oda, T.; Chino, K.; Kanehisa, H.; Fukunaga, T.; Kawakami, Y. (International Journal of Sport & Health Science, 2005)
The fascicle lengths of the human gastrocnemius muscle during isometric plantar flexions were analyzed using a three-dimensional ultrasound system (3D-US). Prior to measurements in vivo, the accuracy and reproducibility of the 3D-US were examined by taking images of a phantom. The horizontal errors were 0.3 - 1.0%, and the vertical errors were 1.2 - 1.6%. In addition, the coefficients of variance for the repeated measurements were 3.3% and 1.7% for horizontal and vertical directions, respectively. Second, both at rest and each of five intensities {20,40,60,80,100% of maximum voluntary contraction (MVC)}, at a fixed ankle joint angle of 90deg, the 3D-US images of gastrocnemius muscles were obtained and used to determine fascicle length. The fascicle length was also measured using two-dimensional ultrasound system (2D-US), and the values obtained by 2D-US were used to make comparisons with those by 3D-US. From rest to MVC, the fascicle length decreased as a function of relative torque levels from 6.0 (± 0.5) cm to 3.1 (± 0.4) cm with 3D-US, and, in a similar manner, from 5.6 (± 0.5) cm to 3.0 (± 0.4) cm with 2D-US. Thus the present study indicated the accuracy and reproducibility of the 3D-US measurements and its usefulness for determining the fascicle lengths of human muscles in three-dimensional space. The fascicle length measurements determined by 3D-US were, however, significantly longer than those of 2D-US.